Specific adaptations of elbow muscles during extension movements in trained water polo players - Lecompte, J.; Maisetti, O.; Cornu, C.; Portero, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
dominant arm during throwing and swimming periods involving bilateral concentric muscle actions. Surprisingly, there are to date a paucity of studies about the physical demands and mechanical adaptations associated to water polo training and competition (3, 5). Therefore, the present cross-sectional study was designed to evaluate neuromechanical adaptations to WP training in dominant and non-dominant elbow flexor and extensor muscles. Methods. Six non-trained healthy men (C) and six National level water polo field players (WP) were tested on a isokinetic dynamometer at 8 angular velocities (-120°.s-1 to 240°.s-1) and during maximal isometric flexions and extensions at an elbow angle of 90°. The stiffness index (SI) of elbow flexors of the dominant arm, calculated as the slope of the linear musculo-tendinous stiffness vs angular torque relationship, was also evaluated at two elbow angles 90° (ICC = 0.76) and 60° (ICC = 0.5) using the quick-release technique (4). Amplitude of surface EMG (RMS-SEMG) of biceps brachii (BB) and triceps brachii (TB) muscles were also recorded. In situ, the maximal velocity of the ball at release was determined with a radar during penalty throws for WP players. Results. WP elbow flexors were significantly stronger than C (+27%, P<0.01), without difference in the torque/angular velocity (T/AV) relationship shape. No between-group differences were observed for agonist (BB) and antagonist (TB) SEMG activity. WP elbow extensor torques were also higher than C (+28%, P<0.01). However, eccentric torques (-60°.s-1) were higher than isometric and slow concentric torques (30°.s-1) only for WP (Fig.1). Moreover, the agonist (TB) RMS-SEMG seemed to be higher for WP than their counterparts (+14%; P = 0.11) whereas, BB coactivation level was higher for non-trained group under eccentric conditions (+70%; P<0.001) (Fig.2). Furthermore, these results were not dependant upon laterality. SI (means ± SE) calculated in flexion at 90° were 21 ± 2 rad-1 and 22 ± 2 rad-1 for WP and C respectively; and at 60° were 18 ± 5 rad-1 and 23 ± 4 rad-1 for WP and C respectively. SI seemed to be lower (-14%, P>0.05) for WP compared to C irrespective of elbow angle. SI seemed to be lower at 60° compared to 90° for WP. The estimated ball velocities at release during penalty throws ranged of 65-68 km.h-1 but was not correlated to torques or SI. Discussion/Conclusion. Our results showed that intensive water polo training induced specific adaptations to elbow extensor torques by changing the classical "plateauing" in the slow eccentric velocities - high torque region (1). Decrease in antagonist coactivation level (2) and higher agonist activation (6) are likely to mediate these adaptations of elbow muscles during high extension torques in water polo players. Furthermore, we did not find any significant differences in terms of laterality and active stiffness of elbow flexor muscles suggesting that swimming training probably overcomes the potential lateral specificity induced by the repetitive use of dominant arm in throwing.